2020
DOI: 10.1039/c9nh00414a
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on the effects of gamma radiation on the physical properties of a two-dimensional WS2monolayer semiconductor

Abstract: This article reports the effects of gamma radiation on the structural, optical and magnetic properties of monolayer tungsten disulfide (WS2) grown by a scalable van der Waals epitaxial (VdWE) process on a SiO2 coated Si substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…Both the valley degeneracy breaking driven by SOC and the excitonic correction in the optical properties may be explored to tune the power conversion efficiency in that compounds. We presented results that show good agreement with experimental data, for exciton energy or exciton binding energy.…”
Section: Discussionmentioning
confidence: 99%
“…Both the valley degeneracy breaking driven by SOC and the excitonic correction in the optical properties may be explored to tune the power conversion efficiency in that compounds. We presented results that show good agreement with experimental data, for exciton energy or exciton binding energy.…”
Section: Discussionmentioning
confidence: 99%
“…The few-layer WS 2 film sample was prepared by Van der Waals epitaxy (VdWE) process. [49][50][51] In this process, WCl 6 (99.9% pure from Sigma-Aldrich) was kept in a bubbler at room temperature, and WCl 6 vapour was delivered by argon gas through a mass flow controller (MFC) to the VdWE quartz reaction tube. The reactive gas, H 2 S, was delivered through second MFC and then mixed with another argon gas through a third MFC.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Using a 60 Co source, Felix et al irradiated 1 L WS 2 crystals with an absorbed dose of 400 Gy and observed ferromagnetic hysteresis, which they attributed to a defect configuration involving one W and two S vacancies. 28 Vogl et al exposed various 1 L group VI TMDC crystals, produced by micromechanical exfoliation (MME), 29 to gamma radiation using a 22 Na source. 30 Although the photoluminescence (PL) spectrum of MoS 2 , MoSe 2 , and WSe 2 changed negligibly with increasing dose, a significant linear increase in the PL intensity was observed for WS 2 crystals as a function of radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have evaluated the effect of gamma irradiation on the physical properties of 2D group VI TMDCs. Using a 60 Co source, Felix et al irradiated 1 L WS 2 crystals with an absorbed dose of 400 Gy and observed ferromagnetic hysteresis, which they attributed to a defect configuration involving one W and two S vacancies . Vogl et al exposed various 1 L group VI TMDC crystals, produced by micromechanical exfoliation (MME), to gamma radiation using a 22 Na source .…”
Section: Introductionmentioning
confidence: 99%